Labor Market Duality in Korea - Schauer, Johanna (IMF Working Papers; Working Paper ;, 2018)
Labor market duality is a complex and critical issue for many countries that can lower productivity, contribute to inequality and result in negative externalities. In this paper, I study duality in the Korean labor market and analyze its sources and potential policy options. I find that employment protection legislations and large productivity differentials are the key drivers of Korea's duality. In addition, applying a general equilibrium search-and-matching model and calibrating it to the Korean economy, I show that well-calibrated flexicurity policies can significantly reduce duality and inequality and raise welfare and productivity. Notably, the introduction of all three pillars-flexiblity, a strong safety net and active labor market policies-is critical for its success. If only one pillar is introduced it can result in negative side-effects and might not reduce duality.